Was Jerusalem a fortified stronghold in the Middle Bronze Age? — an alternative view. (3rd May 2016) - Ussishkin, David
Abstract : Segments of massive walls identified as city walls dated to the Middle Bronze II (MB II) period were uncovered on the eastern slope of the City of David by Kathleen Kenyon, and later by Yigal Shiloh. A massive fortifications complex was uncovered in the area of the Gihon Spring by Ronny Reich and Eli Shukron, this too was dated to the MB II period. New analysis of the data from all three excavation projects possibly indicates that these fortifications date to the Iron II B–C period, to the 8th–7th centuries BC, rather than the MB II. This suggestion cannot be conclusively proven and it is presented here as an alternative concept to the current, generally accepted one. If that is so MB II Jerusalem was an unfortified settlement. The 'Cyclopean' city wall in Tell Rumeidah/ancient Hebron, usually dated to the MB II is discussed at the end of the paper. It is argued that this wall too possibly dates to Iron II B–C rather than MB II.